Structural change and sectoral interlinkages in the Saudi economy: An input–output analytical approach - Khababa, Nourredine; Brika, Said khalfa; Adli, Brahim; Bengana, Ismail (International Journal of Innovative Research and Scientific Studies, 2025)
Identifying the forces that create the structural transformation of the economic landscape of Saudi Arabia is key to developing appropriate policies and strategies. The difficulty of this task increases with the interdependencies inherent in a modern economy. To provide an understanding of the sources of structural change within the Saudi economy, an input-output analysis approach was employed. This methodological framework enabled the estimation of changes within individual sectors as well as inter-sectoral linkage changes. This analysis showed that there are considerable variations in the pattern of changes among the sectors. A firm’s self-reliance in the production of intermediate goods indicates that agriculture, water supply, and health services are largely driven by internal factors. In contrast, the information and professional services sectors show changes predominantly as a result of sectoral interactions with other sectors. The input-output analysis presented the different forms or sources of input-output structural change of different Saudi economic sectors, which are important for formulating sectoral strategies. Hence, it helps to devise such policies that would empower the economy to grow robustly while minimizing the adverse effects of internal and external changes on the synergies across the sectors of the economy.